PM2.5 Magnetic Properties in Relation to Urban Combustion Sources in Southern West Africa - Aruã da Silva Leite; Jean-François Léon; Melina Macouin; Sonia Rousse; Ricardo Ivan Ferreira da Trindade; Arnaud Proietti; Loïc Drigo; Paul Yves Jean Antonio; Aristide Barthélémy Akpo; Véronique Yoboué; Cathy Liousse (Atmosphere, 2021)
The physico-chemical characteristics of particulate matter (PM) in African cities remain poorly known due to scarcity of observation networks. Magnetic parameters of PM are robust proxies for the emissions of Fe-bearing particles. This study reports the first magnetic investigation of PM2.5 (PM with aerodynamic size below 2.5 μm) in Africa performed on weekly PM2.5 filters collected in Abidjan (Ivory Coast) and Cotonou (Benin) between 2015 and 2017. The magnetic mineralogy is dominated by magnetite-like low coercivity minerals. Mass normalized SIRM are 1.65 × 10−2 A m2 kg−1 and 2.28 × 10−2 A m2 kg−1 for Abidjan and Cotonou respectively. Hard coercivity material (S-ratio = 0.96 and MDF = 33 mT) is observed during the dry dusty season. Wood burning emits less iron oxides by PM2.5 mass when compared to traffic sources. PM2.5 magnetic granulometry has a narrow range regardless of the site or season. The excellent correlation between the site-averaged element carbon concentrations and SIRM suggests that PM2.5 magnetic parameters are linked to primary particulate emission from combustion sources.